2005
DOI: 10.1261/rna.7234205
|View full text |Cite
|
Sign up to set email alerts
|

Functional specificity of shuttling hnRNPs revealed by genome-wide analysis of their RNA binding profiles

Abstract: Nab2, Npl3, and Nab4/Hrp1 are essential RNA binding proteins of the shuttling hnRNP class that are required for the efficient export of mRNA. To characterize the in vivo transcript specificity of these proteins, we identified their mRNA binding partners using a microarray-based assay. Each of the three proteins was coimmunoprecipitated with many different mRNA transcripts. Interestingly, each protein exhibits preferential associations with a distinct set of mRNAs. Notably, some of these appear to denote specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 61 publications
11
88
0
Order By: Relevance
“…1d). That Npl3 rather binds to bulk mRNAs was also published earlier 26 . Furthermore, in support of our data, a preferential association of Gbp2 with unspliced transcripts was recently also identified by a transcriptome-wide technique termed CRAC (crosslinking and analysis of cDNA) 27 .…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…1d). That Npl3 rather binds to bulk mRNAs was also published earlier 26 . Furthermore, in support of our data, a preferential association of Gbp2 with unspliced transcripts was recently also identified by a transcriptome-wide technique termed CRAC (crosslinking and analysis of cDNA) 27 .…”
Section: Resultsmentioning
confidence: 54%
“…Together, all data indicate a model in which Npl3 associates with bulk mRNAs, recruited by RNA polymerase II 21,26 . In case of the intron-containing transcripts it participates in the recruitment of the early spliceosome 22 .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, preferential interaction of mRNAs with certain RNA-binding proteins may dictate the fate of certain classes of mRNAs. In fact, it has been shown that different classes of mRNAs preferentially bind specific subsets of RNA-binding proteins (44), which could contribute to differential mRNA export. Thus, the selective nuclear retention of mRNAs encoding antiviral proteins in Nup98 and Rae1 mutant cells further indicate a role for these proteins in regulating innate and adaptive immunity and demonstrate the underlying complexity of the selective export of distinct mRNA species.…”
Section: Influenza Virus Virulence Correlates With Impaired Mrna Exportmentioning
confidence: 99%
“…Although all conventional Pabs interact with RNA through RRM domains (24), there is evidence to suggest that at least one other type of RNA binding motif may confer specific binding to polyadenosine RNA (9,(25)(26)(27). The yeast protein, nuclear poly(A) binding protein 2 (Nab2), lacks RRM domains and instead contains two other potential RNA binding motifs, an arginine-glycineglycine (RGG) repeat domain and seven tandem CCCH zinc fingers (25,28).…”
mentioning
confidence: 99%